Transformative experiences in tourism: where, when, with whom, and how does tourists' transformation occur? - Godovykh, Maksim (Frontiers in Sustainable Tourism, 2024)
Travel experiences have the potential to induce significant changes in tourists. This perspective paper aims to delineate directions for understanding the where, when, with whom, and why of transformative experiences in tourism, proposing future research directions across various dimensions of this multifaceted topic. The Transformative Experience Diagram is presented as a guide to addressing questions about where, when, with whom, and why travel transformation occurs. These propositions are grounded in a literature review spanning various disciplines, along with authors' quantitative and qualitative studies on the process of travel transformation and discussions with experts from diverse fields. Additional data, gathered from semi-structured interviews with people who previously had transformative travel experiences, inform the discussion on key questions of travel transformation and support the propositions for future research. In addition to conceptualizing the process of tourist transformation and proposing a framework for future research, this perspective paper has the potential to influence tourism management practices by guiding the design of experiences that trigger tourists' transformation, positively impacting personal growth, and enhancing the wellbeing of travelers.